INFLUENCE OF SPATIAL DISTRIBUTION OF CHARGES ON THE FORMATION OF THE BULK PROFILE - VOROBYOV, VIKTOR; VOROBIOVA, LARISA; PASTUSHENKO, RUSLAN; SOLOVEY, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Purpose. The drilling and blasting method is widely used in modern technologies such as mining, slope development for hydroelectric facilities, slope profile stabilization during highway and railway construction, preparation of foundations for the construction of nuclear power plants, tunnels, etc. Based on this, the study of the influence of the explosive charge (EC) shape and its spatial arrangement in the slope massif on the change in the main parameters of the collapse of the ejected rock mass (mass, length, longitudinal and cross-section) is an urgent problem.Methods. The work uses a comprehensive methodological approach, including analysis of literary sources, laboratory experiments on model materials, recording the spread of soil and geometric parameters of the collapse during an explosion on a slope using high-speed filming.Results. Processing of the experimental results showed a significant influence of the charge shape and its spatial arrangement on the final results of the explosion. The experiments conducted revealed that the use of curvilinear charges allows controlling the profile of the pile: compared to the results of the explosion on the ejection of a concentrated charge, the mass of soil placed in the central part increases by 25%, its length increases almost 5 times, the width decreases by 2...3 times, and the height of the pile increases by 3...6 times.Novelty. The work is the first to study the influence of ring charges on the efficiency of a blast on a slope. It has been experimentally established that the optimal charge is a curvilinear charge with a central angle equal to 240o.Practical conclusions. The results of the work can be used in planning drilling and blasting operations to stabilize slopes, as well as in blasting for dumping.
Keywords: blast; explosive; emission; charge; curvilinear; pile; profile; slope; concentrated